Pengaruh Pengaruh Jumlah Tanggungan, Pendapatan, dan Pendidikan terhadap Konsumsi Rumah Tangga Masyarakat Kampung KB ( Studi Kasus: Desa Banua Batung Kecamatan Pandawan Kabupaten Hulu Sungai Tengah) - Amini, Ida; Rudiansyah (PPJP ULM, 2021)
The Effect of Amount of Dependents, Income, and Education on Household Consumption of KB Kampung Communities (Case Study: Banua Batung Village, Padawan Sub-district, Hulu Sungai Tengah District. This study was conducted to (1) analyze the effect of dependents, income, and education on household consumption KB village (family planning), (2) to find out which factors are the most dominant influencing household consumption in the KB community (family planning). The scope of this research is to take a case study in Banua Batung village, Padawan District, Hulu Sungai Tengah Regency. Data obtained from interviews and questionnaires as data from the respondent's polymer totaling 82 people. The data is processed using the help of reviews-9 software with multiple linear regression analysis, which is then tested through the f test (simultaneously) and t-test (partially). The results showed that the number of dependents, income, and education had a significant and positive effect both individually (partially) and together (simultaneously). At the same time, the most dominant factor affecting household consumption in this KB village community was income. Suggestions that should be made to increase income are by developing plantations during the rice farming pause so that land is still used, to emphasize the number of dependents, the government must continue to promote family planning programs, and while to improve education, the government is expected to make various scholarship programs so that rural children this is motivated for school.